Perancangan Interior Loving Hut di Surabaya - Gunawan Wibisono; Cok Gede Padmanaba; Grace Mulyono (Intra, 2015)
Many people begins to realize the importance of health. Especially in terms of food which has become one of the causes of disease sources. People began to switch to air-vegetarian Decreases the risk of disease. Loving Hut is a special restaurant that serves vegetarian food. In which the restaurant in Surabaya is still limited in number and needs to be developed to meet the needs of the people.4